Cerebral 5-HT(2A) receptor and serotonin transporter binding in humans are not affected by the val66met BDNF polymorphism status or blood BDNF levels - Klein, Anders Bue (Nature Publishing Group, 2010)
Recent studies have proposed an interrelation between the brain-derived neurotrophic factor (BDNF) val66met polymorphism and the serotonin system. In this study, we investigated whether the BDNF val66met polymorphism or blood BDNF levels are associated with cerebral 5-hydroxytryptamine 2A (5-HT(2A)) receptor or serotonin transporter (SERT) binding in healthy subjects. No statistically significant differences in 5-HT(2A) receptor or SERT binding were found between the val/val and met carriers, nor were blood BDNF values associated with SERT binding or 5-HT(2A) receptor binding. In conclusion, val66met BDNF polymorphism status is not associated with changes in the serotonergic system. Moreover, BDNF levels in blood do not correlate with either 5-HT(2A) or SERT binding.